Behavior of Fiber-Reinforced Polymer-Confined High-Strength Concrete under Split-Hopkinson Pressure Bar (SHPB) Impact Compression - Xie, Zhihong; Duan, Zhijian; Guo, Yongchang; Li, Xiang; Zeng, Junjie (Applied sciences, 2019)
Fiber-reinforced polymer (FRP) has become increasingly popular in repairing existing steel-reinforced concrete (RC) members or constructing new structures. Although the quasi-static axial compression performance of FRP-confined concrete (FCC) has been comprehensively studied, its dynamic compression performance is not well understood, especially the dynamic compressive behavior of FRP-confined high-strength concrete (FCHC). This paper presents an experimental program that consists of quasi-static compression tests and Split-Hopkinson Pressure Bar (SHPB) impact tests on FRP-confined high-strength concrete. The effects of the FRP types, FRP confinement stiffness, and strain rate on the impact resistance of FCHC are carefully studied. The experimental results show that the strain rate effect is evident for FRP-confined high-strength concrete and the existence of the FRP greatly improves the dynamic compressive strength of high-strength concrete. An existing strength model is modified for impact strength of FCHC and the predicted results are compared with the test results. The results and discussions show that the proposed model is accurate and superior to the existing models.